An estimate of ⁴⁷Sc photonuclear yield in a production target - Dikiy, N.P.; Lyashko, Yu.V.; Shevchenko, V.A.; Tenishev, A.Eh.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2020)
⁴⁷Sc is considered as a promising beta-emitter for cancer immunotherapy. For its carrier-free production, the ⁴⁸Ti(γ,p) ⁴⁷ Sc reaction in the field of bremsstrahlung radiation of an electron accelerator can be used. On the basis of developed analytical model and a double-foil activation technique, the main characteristics of the photonuclear isotope production and optimal dimensions of a production target have been established. The measured photonuclear yield of ⁴⁷Sc and dominant scandium admixtures in thin foils of natural titanium in the electron energy range of 35 to 95 MeV enabled to specify the available data on the cross-section of the ⁴⁸Ti(γ,p)⁴⁷Sc reaction. Using those results, the gross and specific activity of ⁴⁷Sc in the cylindrical titanium targets of optimal size were calculated by a simulation technique. The comparison of capacity of the photonuclear method of the ⁴⁷Sc production with other techniques is carried out.